Poverty, Education, and Decent Work Rates in Central and Eastern EU Countries - Alexandra Ciucu; Vanesa Vargas; Carmen Păuna; Adina-Iuliana Jigani (Standards, 2025)
Poverty is a major concern worldwide, and so its eradication represents the first Sustainable Development Goal. Moreover, quality education and decent working conditions are among the factors that seem to reduce poverty, a detail also observed in the current research. The current study aimed to determine poverty and educational levels along with work conditions within the 11 EU Member States located in Central and Eastern Europe using 2023 Eurostat data. To identify them, two techniques were implemented: cluster analysis and the TOPSIS method. The first is used to determine similarities and differences between countries, and the second is used with the purpose of achieving a ranking of the countries based on the 10 indicators designed to examine the three SDGs investigated. Among the results discovered, the clear differentiation of Romania and Bulgaria compared to the other countries was observed for most of the indicators analysed, especially for the people in severe material and social deprivation, as well as the share of individuals having at least basic digital skills. Thus, by applying both methods, the grouping of Romania and Bulgaria is obvious, with these countries being characterised by the poorest performances within the analysed countries. At the opposite end of the scale was Slovenia, which presented the lowest values of the indicators intended to define poverty for the year evaluated, standing out among the countries with the best results for most of the indicators included in the analysis.